Impactos de choques de preferências em um modelo de ciclos reais de negócios no Brasil - Linhares, Gerson Guilherme Lima (2018)
This dissertation analyzes the impacts of intertemporal and intratemporal preferences shocks on the Brazilian economy, in particular for the variables output, consumption, investment, hours of work, wages and government spending. We use a dynamic stochastic general equilibrium model (DSGE) of the type of real business cycles with government taxing in a distorting way and four shocks: intertemporal, intratemporal preferences shocks, productivity and shock in proportion to government spending. We use annual data with calibration, the idea based on Nakajima (2005) and Sims (2016a) was used to compare preference shocks through impulse response functions and variance decomposition to compare the volatility of the variables given the four shocks to achieve the objective. The main results are: the intertemporal preference shocks increases consumption, salaries and reduce the investment, the hours of work, government spending and output; the intratemporal preference shocks contributed to the increase of wages and reduction of the other variables; while productivity shocks led all variables to increase and shocks to the proportion of government expenditures had the crowding out expected effect in the new-classical literature. Finally, using the variance decomposition of variables, we find that intratemporal preference shocks contributed more to the variability of product, hours of work, wages and government spending than intertemporal preferences shocks. The productivity shock was the most important one to explain the variability of output and wages. The shock in the proportion of government spending was among the four shocks which further explained the variability of consumption, investment, and government spending.